THE INFLUENCE OF WOMEN'S INVOLVEMENT ON COMPANY PERFORMANCE WITH COMMITMENT AS A MODERATING VARIABLE - Titin; Muhamad Risal Tawil; Rieneke Ryke Kalalo; Atikah Dewi Utami; Melati Dama (Adisam Publisher, 2024)
Researchers believe that women's involvement will be able to have a positive relationship and have a significant influence on company performance because women have endurance, detailed attitudes, and so on compared to men in general. This research is quantitative research with an exploratory approach related to Employee Engagement, Company Performance, and Commitment as a source of energy to find novelty in the research being conducted. The data used in this research is quantitative data that researchers distributed to 450 employees of Pt. Waskita is spread throughout Indonesia with a minimum criteria of working for 6 months. This data was obtained by distributing questionnaires online and ultimately analyzed by the smart PLS 4.0 analysis tool. The result in this research show that the Women's Involvement variable can have a positive relationship and a significant influence on Company Performance because the P-Values value is positive and is below the 0.05 significance level, namely 0.022. Apart from that, as a second hypothesis, the researchers also believe that the Commitment variable can strengthen the influence of the Women's Involvement variable on Company Performance because basically women are detailed and diligent, and will be even more detailed and diligent if accompanied by strong commitment. So the results of the second row of table 3 of the Jlaur Coefficient in the research show that the Commitment variable can moderate this influence because the P-Values value is below the significance level of 0.05, namely 0.000, which is more significant than the direct test of 0.022. Thus, the first and second hypotheses in this study can be accepted.